Uncommon but imperative cause of repeated acute stent thrombosis: Kounis syndrome type III. Issue 3 (1st March 2021) - Miura, Shiro; Yamashita, Takehiro; Murata, Masaki; Kounis, Nicholas G
Abstract : A 69-year-old woman with a history of allergic reactions to unknown metals who presented 1 year prior with acute coronary syndrome complicated by acute stent thrombosis (ST) was admitted due to new-onset chest pain during mild exercise. She electively underwent coronary angiography, revealing a newly developed stenosis in the fourth branch of the posterior descending artery, treated with an everolimus-eluting stent. One hour later, she reported of sudden chest tightness and nausea; ECG revealed significant ST-segment elevation in the II, III and aVF leads. We suspected ST-segment elevation myocardial infarction resulting from an allergic reaction (ie, Kounis syndrome type III) and managed it properly by eliminating other potential causes. The tentative diagnosis was confirmed by pathological examination of aspirated materials. Kounis syndrome type III may be a frequently undiagnosed clinical entity, emphasising the importance of pathological examination of aspirated materials when implanting coronary stents and history-taking of allergies to stent metals.